Alignment-free protein interaction network comparison. - Ali, W; Rito, T; Reinert, G; Sun, F; Deane, C (Oxford University Press, 2014)
MOTIVATION: Biological network comparison software largely relies on the concept of alignment where close matches between the nodes of two or more networks are sought. These node matches are based on sequence similarity and/or interaction patterns. However, because of the incomplete and error-prone datasets currently available, such methods have had limited success. Moreover, the results of network alignment are in general not amenable for distance-based evolutionary analysis of sets of networks. In this article, we describe Netdis, a topology-based distance measure between networks, which offers the possibility of network phylogeny reconstruction. RESULTS: We first demonstrate that Netdis is able to correctly separate different random graph model types independent of network size and density. The biological applicability of the method is then shown by its ability to build the correct phylogenetic tree of species based solely on the topology of current protein interaction networks. Our results provide new evidence that the topology of protein interaction networks contains information about evolutionary processes, despite the lack of conservation of individual interactions. As Netdis is applicable to all networks because of its speed and simplicity, we apply it to a large collection of biological and non-biological networks where it clusters diverse networks by type. AVAILABILITY AND IMPLEMENTATION: The source code of the program is freely available at http://www.stats.ox.ac.uk/research/proteins/resources. SUPPLEMENTARY INFORMATION: Supplementary data are available at Bioinformatics online.